Evaluation of different aonla (Emblica officinalis) cultivars under rainfed conditions of lower shivalik foothills of Himalayas - BAKSHI, PARSHANT; WALI, V K; JASROTIA, AMIT; SHARMA, AKASH; IQBAL, MUDASIR (The Indian Journal of Agricultural Sciences, 2015)
Six cultivars of aonla (Emblica officinalis Gaertn), viz. Banarasi, Chakaiya, Neelam, Francis, Kanchan and Desi were evaluated for growth, yield and quality parameters. In all the cultivars of aonla, flowering started in the month of April. The cultivar Desi flowered early (1st week of April), whereas Kanchan and Neelam were found to be late in flowering (2nd week of April). The cultivar Banarasi had longest flowered period (24 days) while Neelam and Kanchan had shortest (20 days). The total number of flowers was higher in cultivars Banarasi (816) and Desi (842). The lowest sex ratio was recorded in Neelam (79.40:1) followed by Chakaiya (95.84:1) and highest in Desi (186.10:1) owing to higher percentage of female flowers in Neelam (1.25%) and minimum in Desi (0.53%). Maximum fruit setting of 51.86% was found in Neelam and minimum (20.16%) in Desi. Among the different cultivars studied, minimum fruit drop of 48.14% was recorded in Neelam and maximum (79.84%) in Desi cultivar. The study revealed that cultivar Neelam was superior to all other cultivars in terms of yield attributes as it registered highest average yield of 72.77 kg/ plant. From the various physical characteristics studied, cultivar Neelam showed significantly maximum fruit weight (41.46 g), fruit length (3.73 cm), fruit diameter (4.42 cm), fruit volume (39.80 cm3), pulp weight (39.57 g), stone weight (1.89 g) and pulp:stone ratio of 20.94. The cultivar Neelam was found superior in terms of chemical characteristics of fruit such as vitamin-C (596.03 mg/100g pulp), total sugars (5.71%), reducing sugars (3.41%), nonreducing sugars (2.19%), TSS:acid ratio (6.54). Specific gravity of 1.13, TSS (12.200B) and acidity of 2.08 was found maximum in Desi aonla. From the present investigation it can be concluded that Neelam cultivar of aonla is most superior under the rainfed conditions.